Comparing the impact of Hydroxychloroquine based regimens and standard treatment on COVID-19 patient outcomes: A retrospective cohort study - Saja H. Almazrou; Ziyad S. Almalki; Abdullah S. Alanazi; Abdulhadi M. Alqahtani; Saleh M. Alghamd (Elsevier, 2020)
Background: Pharmacological treatments including antivirals (Lopinavir/Ritonavir), Immuno-modulatory and anti-inflammatory drugs including, Tocilizumab and Hydroxychloroquine (HCQ) has been widely investigated as a treatment for COVID-19.Despite the ongoing controversies, HCQ was recommended for managing mild to moderate cases in Saudi Arabia . However, to our knowledge, no previous studies have been conducted in Saudi Arabia to assess its effectiveness. Methods: A hospital-based retrospective cohort study involving 161 patients with COVID-19 was conducted from March 1 to May 20, 2020. The study was conducted at Prince Mohammed bin Abdul Aziz Hospital (PMAH).The population included hospitalized adults (age ≥ 18 years) with laboratory-confirmed COVID-19. Each eligible patient was followed from the time of admission until the time of discharge. Patients were classified into two groups according to treatment type: in the HCQ group, patients were treated with HCQ; in the SC group, patients were treated with other antiviral or antibacterial treatments according to Ministry of Health (MOH) protocols.The outcomes were hospitalization days, ICU admission, and the need for mechanical ventilation.We estimated the differences in hospital length of stay and time in the ICU between the HCQ group and the standard care (SC) group using a multivariate generalized linear regression. The differences in ICU admission and mechanical ventilation were compared via logistic regression. All models were adjusted for age and gender variables. Results: A total of 161 patients fulfilled the inclusion criteria. Approximately 59% (n = 95) received HCQ-based treatment, and 41% (n = 66) received SC. Length of hospital stay and time in ICU in for patients who received HCQ based treatment was shorter than those who received SC. Similarly, there was less need for ICU admission and mechanical ventilation among patients who received HCQ based treatment compared with SC, (8.6% vs. 10.7 and 3.1% vs. 9.1%). However, the regression analysis showed no significant difference between the two groups in terms of patient outcomes. Conclusion: HCQ had a modest effect on hospital length stay and days in ICU compared with SC. However, these results need to be interpreted with caution. Larger observational studies and RCTs that evaluate the efficacy of HCQ in COVID-19 patients in the Saudi population are urgently needed.